Sequencing Carbon Dioxide Removal into the EU ETS - Darius Sultani; Sebastian Osorio; Claudia Günther; Michael Pahle; Katrin Sievert; Tobias S. Schmidt; Bjarne Steffen; Ottmar Edenhofer (CESifo GmbH, 2024)
Novel Carbon Dioxide Removal (CDR) technologies have seen a first wave of deployment, driven by investments through voluntary carbon markets and by specific support policies. To sustain the momentum, a credible long-term policy path is urgently needed to lead removal technologies through the valley of death, and to ramp-up sufficient capacities to limit global warming to well below 2°C. The integration of removals into carbon compliance markets has been widely discussed as a potential option. Even though current allowance prices in markets like the European emissions trading system (EU ETS) are still considerably lower than removal cost, integration and the prospects of rising allowance prices could increase long-term certainty for investors. What is more, integration would also help to find to the efficient mix of emissions abatement and removal. To date, however, it remains unclear how exactly such an integration can take place. We address this gap in three parts. We (1) characterise a first-best vision for removals in the form of an economically desirable, long-term regulatory framework to work towards to. We (2) then analyse the implications of a first-best - i.e. direct and unconstrained - integration of permanent removals into the EU's carbon compliance market using the numerical model LIMES-EU. In our base scenario, we find more than 60 Mt of CDR entering the market annually by 2050, cutting allowance prices considerably. This underpins the general cost-effectiveness of integration. However, high uncertainty on CDR cost and fragmented regulation give rise to the risks of abate-ment deterrence and excessive biomass use, which need to be accounted for through a second-best sequencing approach. We consequently (3) derive a three-stage path for removal integration into the EU ETS, based on risk reduction contingencies that serve as preconditions for entering subsequent stages.
Keywords: H23; Q52; Q55; Q58; 330; carbon dioxide removal; emissions trading; policy sequencing; technology learning